The legal regime of collective marks in Spain : its significance for the agricultural sector (2022)
Collective trademarks are distinctive signs of special relevance at the national context. They are essential in the process to distinguish products and services from their similar in the market. The epicenter of this research is the analysis of the theoretical-legal bases to guarantee the protection of collective trademarks in Spain in order to improve the current regime. The use of collective trademarks for the business sector has not been widely used in the national context, especially in relation to SMEs, either due to ignorance or the legal bases that inform their nature and protection. In this sense, the essential aspects for the conceptual definition of the collective trademarks are identified, its current protection system from the comparative and national perspective, as well as the economic importance. Regarding methodology, the use of theoretical, legal - comparative and legal - analytical methods were very useful, as well as the research technique of bibliographic analysis of classic and modern texts, serial and non-serial publications. In correspondence with the study carried out, it was concluded that to improve the system of protection of collective trademarks in Spain, it is necessary to attend to bases such as the principles and objectives of protection, the conceptual definition, the rules of use, the distinction with related figures and the rights conferred.